Measuring the Recovery Orientation of Assertive Community Treatment. (May 2013) - Salyers, Michelle P.; Stull, Laura G.; Rollins, Angela L.; McGrew, John H.; Hicks, Lia J.; Thomas, Dave; Strieter, Doug
BACKGROUND: Approaches to measuring recovery orientation are needed, particularly for programs that may struggle with implementing recovery-oriented treatment.OBJECTIVE: A mixed-methods comparative study was conducted to explore effective approaches to measuring recovery orientation of assertive community treatment (ACT) teams.DESIGN: Two ACT teams exhibiting high and low recovery orientation were compared using surveys, treatment plan ratings, diaries of treatment visits, and team leader–reported treatment control mechanisms.RESULTS: The recovery-oriented team differed on one survey measure (higher expectations for consumer recovery), treatment planning (greater consumer involvement and goal-directed content), and use of control mechanisms (less use of representative payee, agency-held lease, daily medication delivery, and family involvement). Staff and consumer diaries showed the most consistent differences (e.g., conveying hope and choice) and were the least susceptible to observer bias but had the lowest response rates.CONCLUSIONS: Several practices differentiate recovery orientation on ACT teams, and a mixed-methods assessment approach is feasible.